Conserved sequence motifs in the initiator proteins for rolling circle DNA replication encoded by diverse replicons from eubacteria, eucaryotes and archaebacteria. - Ilyina, T V (1992)
An amino acid motif was identified that consists of the sequence HisHydrHisHydrHydrHydr (Hydr--bulky hydrophobic residue) and is conserved in two vast classes of proteins, one of which is involved in initiation and termination of rolling circle DNA replication, or RCR (Rep proteins), and the other in mobilization (conjugal transfer) of plasmid DNA (Mob proteins). Based on analogies with metalloenzymes, it is hypothesized that the two conserved His residues in this motif may be involved in metal ion coordination required for the activity of the Rep and Mob proteins. Rep proteins contained two additional conserved motifs, one of which was located upstream, and the other downstream from the 'two His' motif. The C-terminal motif encompassed the Tyr residue(s) forming the covalent link with nicked DNA. Mob proteins were characterized by the opposite orientation of the conserved motifs, with the (putative) DNA-linking Tyr being located near their N-termini. Both Rep and Mob protein classes further split into several distinct families. Although it was not possible to find a motif or pattern that would be unique for the entire Rep or Mob class, unique patterns were derived for large subsets of the proteins of each class. These observations allowed the prediction of the amino acid residues involved in DNA nicking, which is required for the initiation of RCR or conjugal transfer of single-stranded (ss) DNA, in Rep and Mob proteins encoded by a number of replicons of highly diverse size, structure and origin. It is conjectured that recombination has played a major part in the dissemination of genes encoding related Rep or Mob proteins among the replicons exploiting RCR. It is speculated that the eucaryotic small ssDNA replicons encoding proteins with the conserved RCR motifs and replicating via RCR-related mechanisms, such as geminiviruses and parvoviruses, may have evolved from eubacterial replicons.